A case report: metastasis of melanoma to the heart in an era of immunotherapy. Issue 4 (26th October 2019) - Poulsen, Christian B; Weile, Kathrine S; Schmidt, Henrik; Poulsen, Steen H
Abstract: Background: Cardiac metastasis of melanoma rarely causes heart failure symptoms and the recognition of cardiac involvement is in most cases first established post-mortem. Surgical removal might be considered in selected cases in patients with an inflow or outflow tract obstruction even though the survival remains poor. Frequently, the metastasis cannot be removed and therapeutic options include conventional chemotherapy or immunotherapy, which is currently recommended as first-line treatment. Since the introduction of immunotherapy survival in metastatic disease has significantly increased but data on patients treated for melanoma with cardiac involvement are scarce. Case summary: A 65-year-old man presented with dyspnoea and fatigue. Computed tomography scan revealed tumour processes in the heart, which was confirmed on echocardiography. Biopsies taken from fluorodeoxyglucose positron emission tomography positive lymph nodes in the axilla and groin showed melanoma. Analyses did not reveal BRAF mutation and the PD-L1 expression in tumour cells was below 1%. Treatment with ipilimumab and nivolumab was initiated and cardiopulmonary symptoms subsided during the following months with significant reduction in cardiac metastasis on echocardiography. Unfortunately, the patient developed immune checkpoint inhibitor-induced colitis and could no longer continue on the therapy. Due to development of extra-cardiac and cerebral metastasis, he was referred to palliative care. Discussion: This case demonstrates that timely treatment with immunotherapy could be a safe and effective option for melanoma with cardiac involvement. During treatment, the patient developed severe colitis, a known side effect to immunotherapy. Though this often can be managed with steroids it complicates further treatment.